Decision making deficits in patients with first-episode and chronic schizophrenia. - Hutton, S; Murphy, F; Joyce, E; Rogers, R; Cuthbert, I; Barnes, T; McKenna, P; Sahakian, B; Robbins, T (2002)
A considerable body of evidence suggests that the dorsolateral prefrontal cortex is dysfunctional in schizophrenia. However, relatively few studies have explored the involvement of other areas of the frontal cortex. Research suggests that the orbitofrontal cortex (OFC) plays an important role in decision making processes. We assessed the decision making cognition of first-episode and chronic schizophrenic patients with a novel task sensitive to orbitofrontal dysfunction. Both first-episode and chronic patients with schizophrenia took longer than matched controls to make decisions, and both groups were also impaired on a measure of risk adjustment. The impairment in these measures was more severe in the chronic patients than in the first-episode patients, and only the chronic patients made significantly fewer optimal decisions than controls. These results contribute to increasing evidence of orbitofrontal dysfunction in schizophrenia, and suggest that disease progression or the effects of long term antipsychotic medication may influence performance on this task.